PENGARUH KOMPENSASI, KOMITMEN ORGANISASI DAN JOB INSECURITY TERHADAP INTENTION TO TURNOVER PADA DOSEN SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI (STIE SAK) - Poni Yanita; Erni Masdupi (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The research is proposed to test the influence of compenzation, organization commitmen and job insecurity  to intention to turnover lecture High School of Economics Sakti Alam Kerinci. The population in this research werw lecture High School of Economics Sakti Alam Kerinci. Furthermore, by using the formula Slovin, then elected a sample size of 55 lecture STIE SAK with sample tecnique is used namely Simple Random Sampling. The data which namely primer data and skunder data used in this research. For analyzing data by using path analysis and research hipothesis by using testing t with SPSS version 20 is used to analyze the data. The analyze result shows that the compenzation to cause the positve and significant organization commitmen and job insecurity has no contribution to organization commitmen. The analyze result also shows that the compenzation, organization comitmmen to cause the negative and significant to intention to turnover and job insecurity to cause the positive and significant to intention to turnover. Keywords : Compenzation, Organization Commitmen, Job Insecurity, Intention To Turnover